Heavy Metal Resistance and Biosorption of Acid-Tolerant Yeasts Isolated from Tea Soil - Châu, Ngô Thị Tường (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 4, 2013)
Abstract: The heavy metal resistance and biosorption of two acid-tolerant yeast strains isolated from tea soils in Kagoshima Experimental Station (Japan) were investigated. Cryptococcus sp. AH-13 was more resistant to Cd, Cu, Zn, Co, Hg, Ag, Fe, Mn, Ni (except Pb) on the YG solid medium than Candida palmioleophila KB-6. The resistance to heavy metals in the YG solid medium were higher than those in the liquid medium. When being cultivated in YG liquid medium (pH 3.0) containing various concentrations of heavy metals, the growth of Candida palmioleophila KB-6 was considerably inhibited at 0.05 mM Cd, 0.3 mM Cu and 0.5 mM Zn whilst the growth of Cryptococcus sp. AH-13 in was inhibited at 0.5 mM Cd, 1.5 mM Cu and 1.5 mM Zn. Both types of living and dead cells of Candida palmioleophila KB-6 and Cryptococcus sp. AH-13 could remove heavy metals from their salt solutions. The amount of heavy metals accumulated in above types of yeast cells increases along with the concentration of heavy metals, but seems to be constant at a certain saturable concentration of heavy metals. Heavy metal biosorption by Cryptococcus sp. AH-13 appeared to be higher than that by Candida palmioleophila KB-6. Keywords: T ea soil, acid-tolerant yeast, heavy metal resistant yeasts, Cryptococcus sp. AH-13, Candida palmioleophila KB-6.